The Effectiveness of the Teaching Game Model in Improving Football Passing and Shooting Cooperation - Syarif, Ahmad; Erfayliana, Yudesta (Universitas Islam Negeri Raden Intan Lampung, 2024)
The purpose of this study was to analyze the effectiveness of the teaching game model in improving cooperation in passing and shooting football. The research method used was quantitative with an experimental research type. The research design used was nonequivalent control group design pretest and posttest. The population of the study was all fifth grade students of Madrasah Ibtidaiyah while the research sample was 40 students. Data collection techniques used motor skills tests. Data analysis used a paired t-test while the prerequisite test used normality with Shapiro Wilk and homogeneity tests. The results showed that 40% of students had very good passing skills, while 50% of students showed very good shooting skills. The paired t-test showed significant differences in both variables, with a p-value of less than 0.05, indicating that the intervention succeeded in improving these skills statistically and practically. The results of the normality and homogeneity tests also indicated that the measured data met the assumptions for further analysis. It can be concluded that the teaching game model can improve cooperation in passing and shooting football.